Thermodynamic model for exergetic performance of a tubular SOFC module - Akkaya, Ali Volkan; Sahin, Bahri; Erdem, Hasan Huseyin (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
A tubular solid oxide fuel cell (TSOFC) module fed by methane is modelled and analyzed thermodynamically from the exergy point of view in this paper. The model of TSOFC module consists of mixer. pre-reformer, internal reforming fuel cell group, afterburner and internal pre-heater components. The model of the components forming module is given based on mass, energy and exergy balance equations. The developed thermodynamic model is simulated, and the obtained performance characteristics are compared and validated with the experimental data taken from the literature concerning TSOFC module. For exergetic performance analysis, the effects of operating variables such as current density, pressure, and fuel utilization factor on exergetic performances (module exergy efficiency, module exergetic performance coefficient, module exergy output and total exergy destruction rate, and components' exergy efficiencies, exergy destruction rates) are investigated. From the analysis, it is determined that the biggest exergy loss stems from exhaust gasses. Other important sources of exergy destruction involve fuel cell group and afterburner. Consequently, the developed thermodynamic model is expected to provide not only a convenient tool to determine the module exergetic performances and component irreversibility but also an appropriate basis to design complex hybrid power generation plants. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Tubular SOFC; Modelling; Simulation; Exergetic performance; ECOLOGICAL COEFFICIENT; FUEL; OPTIMIZATION; DESIGN; Science & Technology - Other Topics; Energy & Fuels